Кафедрa ТММ и САПР: к 50-летию факультета транспортного машиностроения - Ткачук, Николай Анатольевич (НТУ "ХПИ", 2015)
Статья посвящена вопросам истории кафедры "Теория и системы автоматизированного проектирования механизмов и машин" Национального технического университета "Харьковский политехнический институт". Описаны вехи развития кафедры. Проиллюстрирован ряд научно-исследовательских работ, которые выполняла кафедра. Описаны научные коллективы и направления их деятельности. Приведены некоторые результаты исследований сложных механических и биомеханических систем. Сформированы перспективные направления развития учебного процесса и научных исследований на кафедре.

The article is dedicated to the questions of history of department "Theory and computer-aided design of mechanisms and machines" of National Technical University "Kharkiv Polytechnic Institute". The landmarks of department’s development are described. The row of research works that was executed by a department is illustrated. Scientific collectives and directions of their activity are represented. Some results over researches of complicated mechanical and biomechanical systems are mentioned. Perspective directions of development of educational process and scientific researches are formed for the department.
The department TMM and SAPR: to the fiftieth anniversary of Transport Engineering Faculty
Keywords: теория механизмов; системы автоматизированного проектирования; научно-исследовательская работа; theory of mechanisms; computer-aided design; development work